Solitary plasmacytoma of bone over sacrum: a case report - Chen, Hsin-Lin; Chou, Ying-Hsiang; Lee, Yueh-Chun; Tseng, Hsien-Chun (Therapeutic Radiology and Oncology, 2019)
Solitary plasmacytoma of bone (SPB), also called osseous plasmacytoma, is more common in males than in females with an estimated ratio of 2:1. The median age of SPB patients is approximately 55 years. Localized radiation therapy is the first-line treatment to avoid progression to multiple myeloma. A 46-year-old man visited our hospital due to lower back pain radiating to his lower limbs for 3 months. L-spine MRI showed S2 to S4 bone erosion with a large (8.8×6.2 centimeter) tumor over sacrum. Following partial tumor removal, pathology showed plasmacytoma. Adjuvant radiotherapy with 50 Gy in 25 fractions was administered to the gross tumor based on volumetric modulated arc therapy (VMAT). No adjuvant chemotherapy was given. Pelvic CT was arranged every 3 months during 24-month follow-up. There was no distant metastasis or newly diagnosed multiple myeloma during the follow-up period.